ACUTE AND CHRONIC RESPONSES TO THE CONVULSANT PILOCARPINE IN DBA/2J AND A/J MICE - WINAWER, M. R. (2007)
Characterizing the responses of different mouse strains to experimentally-induced seizures can provide clues to the genes that are responsible for seizure susceptibility, and factors that contribute to epilepsy. This approach is optimal when sequenced mouse strains are available. Therefore, we compared two sequenced strains, DBA/2J (DBA) and A/J. These strains were compared using the chemoconvulsant pilocarpine, because pilocarpine induces status epilepticus, a state of severe, prolonged seizures. In addition, pilocarpine-induced status is followed by changes in the brain that are associated with the pathophysiology of temporal lobe epilepsy (TLE). Therefore, pilocarpine can be used to address susceptibility to severe seizures, as well as genes that could be relevant to TLE. A/J mice had a higher incidence of status, but a longer latency to status than DBA mice. DBA mice exhibited more hippocampal pyramidal cell damage. DBA mice developed more ectopic granule cells in the hilus, a result of aberrant migration of granule cells born after status. DBA mice experienced sudden death in the weeks following status, while A/J mice exhibited the most sudden death in the initial hour after pilocarpine administration. The results support previous studies of strain differences based on responses to convulsants. They suggest caution in studies of seizure susceptibility that are based only on incidence or latency. In addition, the results provide new insight into the strain-specific characteristics of DBA and A/J mice. A/J mice provide a potential resource to examine the progression to status. The DBA mouse may be valuable to clarify genes regulating other seizure-associated phenomena, such as seizure-induced neurogenesis and sudden death.